Potential for adventure sports tourism in biodiversity zones in Ecuador (RIAF. International Journal of Physical Activity, 2026)
Adventure sports tourism in Ecuador's highly biodiverse areas has become a key option for promoting sustainable economic, social, and environmental development. This study aimed to evaluate the potential of activities such as hiking, rafting, mountain biking, and birdwatching in the country's megadiverse regions, including the Amazon, the Andes, the coast, and the Galapagos Islands. A mixed-method approach was used, combining document analysis with surveys of 250 tourists, both domestic and international, in addition to conducting semi-structured interviews with 30 local stakeholders involved in the tourism and environmental sectors. The results highlighted strengths such as natural wealth, ecosystem diversity, and continuous improvement in road infrastructure, along with challenges such as limited international promotion and a lack of training in host communities. It was also found that adventure tourism has generated sustainable income, fostered ecosystem conservation, and contributed to local well-being in places such as Napo, Chimborazo, and Quito. In conclusion, Ecuador has great potential to become a leading destination for adventure sports tourism, provided comprehensive strategies are implemented to strengthen promotion, optimize the training of local stakeholders, and minimize environmental impacts, aligning with the principles of national sustainable development.
Keywords: Adventure tourism; biodiversity; sustainability; ecotourism; local communities; conservation